2019
DOI: 10.2320/matertrans.mf201927
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Storage in Mg and Mg-Based Alloys and Composites Processed by Severe Plastic Deformation

Abstract: Mg-based hydrides have been extensively studied in the last 20 years due to its great potential as hydrogen storage materials, especially for stationary applications. Severe plastic deformation (SPD) can be used to produce Mg-based materials for hydrogen storage applications, with good activation (first hydrogenation) and H-absorption/desorption kinetics, combined with enhanced air resistance. Both advanced (e.g. highpressure torsion, equal-channel angular pressing) and more conventional (e.g. cold rolling, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…But, two important issues should be taken into account when we select the HEBM as the main processing route to the production nanostructured Mg-based materials with desirable properties for hydrogen storage: a) the HEBM requires longer processing times associated with high energy consumption that increase the total cost of processing; b) the powders obtained by HEBM display high specific surface area, and therefore, they are substantially vulnerable to air contaminants as oxygen or humidity, demanding, a complex handling that should be done under inert atmosphere 12 . In this context, the use of Severe Plastic Deformation (SPD) techniques such as Equal Channel Angular Pressing (ECAP), Cold Rolling (CR) and Friction Stir Processing (FSP) as alternative processing routes for Mg-based materials aiming desirable hydrogen storage properties has been demonstrated to be a successful approach to address these issues [13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…But, two important issues should be taken into account when we select the HEBM as the main processing route to the production nanostructured Mg-based materials with desirable properties for hydrogen storage: a) the HEBM requires longer processing times associated with high energy consumption that increase the total cost of processing; b) the powders obtained by HEBM display high specific surface area, and therefore, they are substantially vulnerable to air contaminants as oxygen or humidity, demanding, a complex handling that should be done under inert atmosphere 12 . In this context, the use of Severe Plastic Deformation (SPD) techniques such as Equal Channel Angular Pressing (ECAP), Cold Rolling (CR) and Friction Stir Processing (FSP) as alternative processing routes for Mg-based materials aiming desirable hydrogen storage properties has been demonstrated to be a successful approach to address these issues [13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the significant benefits, HEBM has some weaknesses in processing nanoscale hydrogen storage alloys, including the problem of scaling-up to the industrial level, exhaustive energy consumption, high production cost and potential fire risk. To address these issues, bulk processing techniques [20] based on severe plastic deformation (SPD) have recently been applied very intensively to obtain hydrogen storage materials with enhanced properties [14,16,21,22]. It was shown that the refinement of grain structure, the formation of high-angle grain boundaries and various lattice defects occurring during the SPD process have beneficial effects on the hydrogen sorption kinetics of the material [14,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, bulk processing techniques [20] based on severe plastic deformation (SPD) have recently been applied very intensively to obtain hydrogen storage materials with enhanced properties [14,16,21,22]. It was shown that the refinement of grain structure, the formation of high-angle grain boundaries and various lattice defects occurring during the SPD process have beneficial effects on the hydrogen sorption kinetics of the material [14,21,22]. The prospect of relatively simple and low cost manufacturing of bulk samples with better air resistance compared to powders makes these SPD techniques a promising supplement to the ball milling process.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, relatively high dehydrogenation temperatures (beyond 600K for MgH 2 ) are directly linked to the strong Mg-H binding energy [3]. The kinetics and mechanisms of metal hydrides formation has been investigated for quite some time [4] and based on this, several approaches have been proposed to improve the kinetics of hydrogen exchange with Mg: i) the introduction of catalysts or alloying elements to favor the dissociation of H 2 molecules or to reduce the binding energy between Mg and H [5], ii) the introduction of crystalline defects to promote the diffusion of hydrogen [6][7][8][9][10][11]. However, Mg and Mg alloys oxidize very quickly even at low temperature and at very low O 2 partial pressure.…”
Section: Introductionmentioning
confidence: 99%